Ablation of Atrial Fibrillation With Pulsed Electric Fields: An Ultra-Rapid, Tissue-Selective Modality for Cardiac Ablation - Reddy, Vivek Y; Koruth, Jacob; Jais, Pierre; Petru, Jan; Timko, Ferdinand; Skalsky, Ivo; Hebeler, Robert; Labrousse, Louis; Barandon, Laurent; Kralovec, Stepan; Funosako, Moritoshi; Mannuva, Boochi Babu; et al. (JACC. Clinical electrophysiology, 2018)
OBJECTIVES: The authors report the first acute clinical experience of atrial fibrillation ablation with PEF-both epicardial box lesions during cardiac surgery, and catheter-based PV isolation. BACKGROUND: Standard energy sources rely on time-dependent conductive heating/cooling and ablate all tissue types indiscriminately. Pulsed electric field (PEF) energy ablates nonthermally by creating nanoscale pores in cell membranes. Potential advantages for atrial fibrillation ablation include: 1) cardiomyocytes have among the lowest sensitivity of any tissue to PEF-allowing tissue selectivity, thereby minimizing ablation of nontarget collateral tissue; 2) PEF is delivered rapidly over a few seconds; and 3) the absence of coagulative necrosis obviates the risk of pulmonary vein (PV) stenosis. METHODS: PEF ablation was performed using a custom over-the-wire endocardial catheter for percutaneous transseptal PV isolation, and a linear catheter for encircling the PVs and posterior left atrium during concomitant cardiac surgery. Endocardial voltage maps were created pre- and post-ablation. Continuous and categorical data are summarized and presented as mean ± SD and frequencies. RESULTS: At 2 centers, 22 patients underwent ablation under general anesthesia: 15 endocardial and 7 epicardial. Catheter PV isolation was successful in all 57 PVs in 15 patients (100%) using 3.26 ± 0.5 lesions/PV: procedure time 67 ± 10.5 min, catheter time (PEF catheter entry to exit) 19 ± 2.5 min, total PEF energy delivery time <60 s/patient, and fluoroscopy time 12 ± 4.0 min. Surgical box lesions were successful in 6 of 7 patients (86%) using 2 lesions/patient. The catheter time for epicardial ablation was 50.7 ± 19.5 min. There were no complications. CONCLUSIONS: These data usher in a new era of tissue-specific, ultrarapid ablation of atrial fibrillation.
Keywords: elektroporace; délka operace; electroporation; Endocardium; Humans; atrial fibrillation; lidé středního věku; venae pulmonales; pulsed electric field; Pericardium; Female; Aged; pulmonary vein isolation; senioři; lidé; Atrial Fibrillation; endokard; katetrizační ablace; catheter ablation; perikard; Operative Time; ženské pohlaví; Male; Middle Aged; Pulmonary Veins; Electroporation; mužské pohlaví; prospektivní studie; Catheter Ablation; fibrilace síní; Prospective Studies